EFFECT OF SOWING DATES ON THE TOBACCO CATERPILLAR [Spodoptera litura (FABRICIUS)], POPULATION, LEAF DAMAGE AND YIELD OF GROUNDNUT - Nath, Paras; Rai, S. N.; Keval, Ram (International Journal of Research -GRANTHAALAYAH, 2017)
The effect of sowing date of groundnut on the population buildup of tobacco caterpillar, Spodoptera litura (Fab.) and its effect on leaf damage (%) and yield was studied at the Agricultural Research Farm of the Banaras Hindu University, Varanasi, Uttar Pradesh, India during rainy season consecutively for three cropping years. The tobacco caterpillar average population and groundnut leaf damage (%) was found maximum in the groundnut crop sown on 20th July followed by 5th July and 20th June during all the three years of study. The first infestation of tobacco caterpillar was observed at 45 days after sowing which disappeared 135 days after sowing. The interaction effect of sowing dates and the periods of observation on the leaf damage was found significant. The yield recorded from groundnut crop sown on 20th June was found maximum while the crop sown on 20th July recorded minimum yield.